Green Chemistry Approaches in Nanocatalyst Development and HPLC Analytic Studies - Rajayan, Jasmin Sajini; Shree, R Dhaniya; Sabrin, O Tawfeeqa; Shameer, B S Muhammad; Kumar, S. Udaya (Journal of Pharmacy Practice and Community Medicine, 2026)
Green synthesis is an eco-friendly method for fabricating nanoparticles using organic matter, such as plants, microorganisms, enzymes, and even biodegradable waste, producing innocuous by-products. Green synthesis advances with safe, environmentally friendly methods that use less energy to build an essential nanoparticle, which plays an important role in the initial binding of a drug to receptors. It consists of many methods with easy ways to follow, to generate a naturally occurring nanoparticle. Green synthesis is followed efficiently to reduce the chemical methods that are hazardous to human health and the environment; it requires less energy and milder conditions than other methods. And other advantages of using green synthesis are ample, and easily accessible materials are used, which is highly cost-effective, and it also ensures safety and is suitable for biomedical applications. So, these nanoparticles are produced by the green synthesis method and are analyzed using High-Performance Liquid Chromatography (HPLC) or high-performance liquid chromatography due to their distinctive properties and possible characterization. Gibbs theory explains that HPLC determination takes place thermodynamically, the proposed thermodynamic approach can be used to describe any type of liquid chromatographic technique, including normal phase, reversed phase, ion exchange and size exclusion chromatography. A method is also presented for the precise determination of dead volume based on disturbance peaks of mobile phase components across the entire concentration range. Additionally, the occurrence of negative capacity factor values for certain compounds is clarified. HPLC is an analytic technique used to separate, identify, or quantify each component in a mixture. HPLC offers a quick, automated, and highly accurate method to identify certain chemical components (Kreuter, 1994).
Keywords: Eco-friendly; Global health; Green chemistry; Immunotherapy; Macromolecule; Synthetic approach